Buket Balon Sebagai Alternatif Buah Tangan Dalam Mengembangkan Kegiatan Kewirausahaan - Dwi Ermayanti Susilo; Ina Nikmatul Chasanah; Ahmad Bihar Isyqi; Wisnu Mahendri; Talitha Zaidah Azmi; Darwin Marasi Purba; Marsinem; Eko Wicaksono (JPM: Jurnal Pengabdian Masyarakat, 2023)
One of the entrepreneurship training activities is making balloon bouquets, which is an alternative souvenir, where later with this innovation in making balloon bouquets, students will be able to develop the entrepreneurial spirit. Balloon bouquets are one alternative business that can be developed currently. A balloon bouquet can be an alternative gift to loved ones as a birthday present, birth, wedding, graduation and so on. Apart from making balloon bouquets, the students are also taught how to do business/commerce, however, the tight business competition means that the students have to try to innovate in making any goods or merchandise that can be used as a business with affordable capital and advances in technological development make it difficult for the students to compete. on the market so that there are still many products sold that are not sold because the packaging and manufacturing methods are still simple and not neat. The aim of this service activity is to help the students of the Annajah Mamba'ul Ma'arif Islamic Boarding School improve their abilities and knowledge in developing creativity, innovation and business marketing through the use of digital technology in finance and marketing. The methods used in this activity are the lecture method, tutorial and mentoring method. The results obtained were that the students of the Annajah Mamba'ul Ma'arif Islamic Boarding School gained an understanding of making balloon bouquets for business with their own creativity as well as an understanding of business management and marketing. Apart from that, the students were proficient and could be creative on their own to develop their talents and skills in making bouquets so that has a high selling value and creates new innovations so that consumers don't get bored with the same bouquet.